Exposure computational models with voxel phantoms coupled to EGSnrc Monte Carlo code - José Wilson Vieira; Viriato Leal Neto; Pedro Henrique Avelino de Andrade; Alex Cristóvão Holanda de Oliveira; Vanildo Júnior de Melo Lima; Isabelle Viviane Batista de Lacerda; Luís Rodrigo Dandrada; Arykerne Nascimento Casado da Silva; William de Souza Santos; Ivan Eufrázio de Santana; Whoody Alem Wanderley Araripe Farias; Larissa Cristina Silva dos Santos; et al. (Brazilian Journal of Radiation Sciences, 2023)
In computational dosimetry of ionizing radiation, the energy deposited in radiosensitive organs and tissues is evaluated when an anthropomorphic simulator (phantom) is irradiated using Exposure Computational Models (ECMs). An ECM is a virtual scene with a phantom positioned mathematically relative to a radioactive source. The initial state includes information like the type of primary particle, its energy, starting point coordinates, and direction. Subsequently, robust Monte Carlo (MC) codes are used to simulate the particle's mean free path, interaction with the medium's atoms, and energy deposition. These are common steps for simulations involving photons and/or primary electrons. The GDN (Research Group on Numerical Dosimetry and the Research Group on Computational Dosimetry and Embedded Systems) has published ECMs with voxel phantoms irradiated by photons using the MC code EGSnrc. This work has led to specific computational tools development for various numerical dosimetry stages, including input file preparation, ECM execution, and result analysis. Since 2004, the GDN developed in-house applications like FANTOMAS, CALDose_X, DIP, and MonteCarlo. Certain previously used phantoms are reintroduced to provide historical context in the ECMs' production timeline, emphasizing additive modifications inherent in systematic theme studies. The dosimetric evaluations used the binary version of the MASH (Male Adult mesh) phantom, converted to the SID (Dosimetric Information System) text file type. This format has been used by the group since 2021 to couple a voxel phantom to the EGSnrc user code. The ECM included an environmental dosimetry problem simulation. Most of these tools are accessible on the GDN page (http://dosimetrianumerica.org).